Website Development and Logo Design Education in Serdang Village, Meranti Subdistrict, Asahan Regency - Fitriani, Annisa; Amelia, Syahputri; Abdillah BB, M; Siregar, Raja Syahmuda; Tuahta, Alexander (Outline Publisher, 2025)
This study aims to develop a village website and provide logo design education for the residents of Serdang Village, Meranti Subdistrict, Asahan Regency. The primary objective of this initiative is to create a digital platform that facilitates information dissemination, promotes local potential such as agricultural products and MSME (Micro, Small, and Medium Enterprises) products, and strengthens digital-based public services. Additionally, the study focuses on enhancing the creative skills of the community, particularly small business owners, through basic graphic design training and logo creation as a visual identity and product branding strategy. The methodology employed in this research is a participatory qualitative approach, combining observation, interviews, and training activities. The website development was conducted collaboratively with village officials to ensure alignment with local needs, while the logo design education was delivered through workshops that included practical sessions on design software usage and creative idea development. Data analysis was carried out descriptively to evaluate the effectiveness of the program. The results indicate that the developed village website functions effectively as both an information dissemination medium and a promotional tool for village potential. Meanwhile, the logo design education successfully enhanced participants’ knowledge and skills in understanding the importance of branding through visual design. Overall, this study demonstrates that digital literacy and creative education can empower village communities, improve the quality of public services, and strengthen the competitiveness of local products in the digital era.